Application of training periodization models by elite judo coaches - Tavares Junior, Antonio Carlos [UNESP]; Drigoade, Alexandre Janotta [UNESP] (Int Scientific Literature, Inc, 2017)
Background and Study Aim: Periodization and structured training models are prominent concepts in the field of sports science. Nevertheless, the structure of the training of Brazilian elite judo athletes and the periodization models used remain unclear. This study investigated how coaches of high-performance judo athletes plan and organise the sports preparation process. Therefore, we aimed to answer the following questions: Do the coaches in this study use sports training periodization to prepare their athletes? Which periodization models do they employ? Is there a preferred periodization model used by this group? Material and Methods: Eight judo coaches took part in this research. The subjects were purposely selected and met at least two of the following inclusion criteria: being a National Club Grand Prix finalist, being coach of the athletes of the Brazilian national team (junior to 18+ years) and being a member of the Brazilian Judo Confederation coaching staff. A semi-structured interview was used for the investigation. Results: The participants were divided into two groups: Group 1, composed of six coaches who adopted a classic periodization model following Matveev's theory and Group 2, consisting of two coaches who used a current periodization model following Verkhoshansky and Tschiene's theories. Conclusions: Our analyses revealed that the coaches in this study applied the precepts of theoretical constructions in sports training periodization as the basis of planning and structuring the training regimen. This sample showed a preference for Matveev's classic periodization model (six out of the eight coaches). Copyright: (C) 2017 the Authors. Published by Archives of Budo
Keywords: combat sport; athletes; training load; qualitative methodology; semi-structured interviews